Nurses\' Knowledge Regarding Evidence-Based Guidelines for Preventing Ventilator-Associated Pneumonia - Hamid Yekta Khotbesara; MohammadReza Yeganeh RastehKenari; Rabiollah Farmanbar; Tahereh Khaleghdoost Mohammadi; Zahra Atrkar Roshan (Journal of Holistic Nursing and Midwifery)
Abstract